A pleasant holiday ending in stonefish poisoning: from paralysis to recovery - Afroze, Samira Rahat; Karmpaliotis, Konstantinos (BIRDEM Medical Journal, 2025)
Stonefish poisoning is considered as one the most venomous poisons encountered in humans. Cases of stonefish poisoning are common in shallow coastal waters of tropical and temperate areas of the Indo-Pacific, Gulf and Arabian sea and rare in non-endemic areas like UK and may be observed only in returning travellers from endemic zones. Here, we present a case of such poisoning, occurring in a British returning traveller from Egypt. The initial treatment was provided in Egypt, while a review and follow up of the case was done in the UK. Our patient suffered from significant morbidity, mostly in the form of neurotoxic and myotoxic manifestations and the recovery was slow. Without prompt and proper treatment, cases like ours can result in complications, even death. As it is common for people to travel, knowledge of such envenomation can be life saving for the affected patient. BIRDEM Med J 2025; 15(3): 141-145